2009
DOI: 10.1136/bjo.2008.155440
|View full text |Cite
|
Sign up to set email alerts
|

Vision-related quality of life and visual function in patients undergoing vitrectomy, gas tamponade and cataract surgery for macular hole

Abstract: Aim: To evaluate the relationship between vision-related quality of life (VR-QOL) and visual function in patients undergoing vitrectomy, gas tamponade and cataract surgery for macular hole (MH). Methods: The 25-item National Eye Institute Visual Function Questionnaire (VFQ-25) was self-administered by 32 patients with MH (age 66.2 (SD 5.4) years) preoperatively and at 3 months postoperatively. Clinical data were collected, including logarithm of minimum angle of resolution (logMAR) best corrected visual acuity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 21 publications
4
45
2
1
Order By: Relevance
“…Similar scores as in RRD surgery have been observed after macula hole surgery (mean VFQ-25 CS 82.4) and epiretinal membrane surgery (83.3) but much lower scores in age-related macular degeneration surgery (54.4). 9,12,16 In this study, VR QOL was at a lower level in patients with RRD than in normal controls even after successful reattachment surgery. In previous studies, a mean VFQ-25 CS after RRD surgery of approximately 80 has been reported.…”
Section: Discussioncontrasting
confidence: 48%
“…Similar scores as in RRD surgery have been observed after macula hole surgery (mean VFQ-25 CS 82.4) and epiretinal membrane surgery (83.3) but much lower scores in age-related macular degeneration surgery (54.4). 9,12,16 In this study, VR QOL was at a lower level in patients with RRD than in normal controls even after successful reattachment surgery. In previous studies, a mean VFQ-25 CS after RRD surgery of approximately 80 has been reported.…”
Section: Discussioncontrasting
confidence: 48%
“…2,7,8,[22][23][24] Moreover, studies investigating visionrelated quality of life in patients undergoing vitrectomy for ERM and other ocular conditions demonstrated a significant improvement in vision and in quality of life. [25][26][27][28] However, it is a common observation that old age is sometimes a barrier for the acceptance of surgery for various ocular conditions. This is probably particularly true for conditions such as ERM, which is often monocular and associated with only moderate visual deterioration, while surgery is associated with a risk for significant complications such as retinal detachment or endophthalmitis.…”
Section: Introductionmentioning
confidence: 99%
“…No significant relationship was found between metamorphopsia scores and visual acuity [72]. Usually after surgery for a macular hole, a decrease in metamorphopsia was reported [73,74]. Krøyer et al [73] suggested that both tangential displacement of the PRs and the eversion of the PRs (due to inner margin eversion) are responsible for metamorphopsia.…”
Section: Metamorphopsia In Vitreoretinal Interface Disordersmentioning
confidence: 99%
“…Metamorphopsia is a common symptom in ERM, macular holes, retinal detachment, and even after successful retinal surgery [13,46,47,48,49,68,69,70,71,72,73,74,75]. Shinoda et al [46 ]correlated the severity of metamorphopsia determined with modified Amsler charts with the subjective score in patients with ERM.…”
Section: Metamorphopsia In Vitreoretinal Interface Disordersmentioning
confidence: 99%